Color influences sensory perception and liking of orange juice - Fernandez-Vazquez, Rocio; Hewson, Louise; Fisk, Ian D.; Hernanz Vila, Dolores; Heredia Mira, Francisco Jose; Vicario, Isabel M.; Hort, Joanne (BioMed Central, 2014)
Background: This study assesses the effect of slight hue variations in orange juice (reddish to greenish) on perceived flavour intensity, sweetness, and sourness, and on expected and actual liking. A commercial orange juice (COJ) was selected as a control, and colour-modified orange juices were prepared by adding red or green food dyes (ROJ and GOJ) that did not alter the flavour of the juice. A series of paired comparison tests were performed by 30 naive panellists to determine the influence of orange juice colour on flavour intensity, sweetness, and sourness. Then, 100 orange juice consumers were asked to rate expected liking of orange juice samples initially by visual evaluation and subsequently for actual liking upon consumption, using a labelled affective magnitude scale. Results: Results of pair comparison tests indicated that colour changes did not affect flavour intensity and sweetness, but the greenish hue (GOJ) significantly increased the perceived sourness. Results of the consumers’ study indicated significant differences in expected liking between the orange juice samples, with ROJ having the highest expected liking. However, scores of actual liking after consumption were not significantly different. COJ and GOJ showed a significant increase in actual liking compared to expected liking. Conclusions: This study shed light on how slight variations in orange juice hue (reddish to greenish hues) affect the perceived flavour intensity, sweetness, and sourness, and the expected and actual liking of orange juice.